Enhancing customers' perceived value in the hotel industry; updated reviews and insights on customer satisfaction on emotional and functional values from a pandemic-era study - Mohd Akhir, Irina; Abd Rahman, Rabiatul Adawiyah; Isa, Nina Farisha; Razali, Mohamad Azli; Mohd Mazlan, Mohd Azreen (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
This research focused on the relationship between perceived value and customer satisfaction in the hotel industry during the COVID- 19 pandemic. The study investigated the association of emotional and functional values with customer satisfaction to review hotel guests’ perspectives during the pandemic. It is imperative for hotel players to direct their attention towards key study areas, due to the swift alterations in the relationship between hotel guest perceived value and satisfaction. This study Aimed in assisting hotel players to effectively identify potential determinants and address unresolved issues pertaining to unmet needs. Data was collected at Grand Alora Hotel in Alor Setar Kedah during the pandemic, utilizing e-survey instrument through cross-sectional study, conducting applied research. Descriptive and correlation test was conducted to review and identify the associations. The finding offers important implications to study further the impact of Covid- 19, where the unprecedented circumstances of pandemic may have significantly altered guest expectations and perceptions until present. The research emphasizes the importance of continuously addressing customers' increased concerns on health and safety during hotel stay. This research contributes to the insights into how hotels can improve their clients’ perceived satisfaction in the future